Islamic Capital Asset Pricing Model: Sebuah Analisis Perbandingan - Igo Febrianto; Artie Arditha Rachman (Jurnal Ilmiah ESAI, 2016)
Moslem investors often find dilemma about asset pricing while having investments in stock exchange.   Conventional asset pricing model, such as Capital Asset Pricing Model (CAPM), cannot accommodate the needs for asset pricing which is free from riba and interest as one of the sharia requirements. The aim of the current research is to compare the conventional model with others which are developed by using zakat and inflation as a replacement component for risk free rate in CAPM, called Islamic CAPM. Descriptive analysis result shows that moslem investors could use inflation as a replacement component for risk free rate.  The statistical evidence also shows that the accuracy of this model is similar to the conventional asset pricing model. Keywords: CAPM, Islamic CAPM, zakat, inflation